Care of children with diabetes as inpatients: frequency of admissions, clinical care and patient experience. Issue 3 (20th February 2013) - Edge, J. A.; Ackland, F.; Payne, S.; McAulay, A.; Hind, E.; Burren, C.; Burditt, J.; Sims, D.
Abstract Aim Hospital inpatient care for children with diabetes is frequently mentioned by parents as unsatisfactory. The aim of this study was to examine the reasons for inpatient admission of children with diabetes and to understand patient and carer experience in order to improve services. Methods Questionnaires were given to medical teams, parents and children during admissions of children with diabetes under 16 years of age in three regions of England. Results There were 401 admissions over 6 months from 3247 patients: 334 (83%) emergency admissions and 59 (15%) elective; the reason is unknown in eight (2%). One hundred and forty‐three (36%) were emergency admissions with diabetic ketoacidosis/hyperglycaemia. Clinical teams reported adverse events around insulin administration in 25, hypoglycaemia (sometimes recurrent) in 120 and food provision in 14 admissions. Others included seven incidents around elective surgery. Diabetes clinical teams were not always informed about admissions and only 33% were informed within 2 h. Parents and children reported fewer problems: 62% were involved in care most of the time and 87% were able to give insulin. Most negative comments were about poor staff management of out‐of‐range blood glucose levels, knowledge of insulin pumps and care of children waiting in the emergency department. Conclusions There were a large number of admissions and the majority were emergencies. Parents generally felt that they receive good care, although with some lack of knowledge amongst the ward staff. There were an unacceptable number of adverse incidents reported. We recommend that education of ward staff in diabetes is carried out regularly with reference to the standards of care.